Endo-sponge in management of anastomotic colorectal leaks: a systematic review and meta-analysis - Dhindsa, Banreet S.; Naga, Yassin; Saghir, Syed M.; Daid, Sarav Gunjit Singh; Chandan, Saurabh; Mashiana, Harmeet; Dhaliwal, Amaninder; Sidhu, Abhitej; Sayles, Harlan; Ramai, Daryl; Bhat, Ishfaq; Singh, Shailender; McDonough, Stephanie; Adler, Douglas G. (Endoscopy International Open, 2021)
Background and study aims Following colorectal surgery, anastomotic dehiscence and leak formation has an incidence of 2 % to 7 %. Endo-SPONGE has been applied in the management of anastomatic leaks (ALs) after colorectal surgery. This is the first systematic review and meta analysis to evaluate the efficacy and safety of Endo-SPONGE in the management of colorectal ALs.Patients and methods The primary outcomes assessed were the technical and clinical success of Endo-SPONGE placement in colorectal ALs. The secondary outcomes assessed were the overall adverse events (AEs) and the AE subtypes. Pooled estimates were calculated using random-effects models with 95 % confidence interval (C. I.). The statistical analysis was done using STATA v16.1 software (StataCorp, LLC College Station, Texas, United States).Results The analysis included 17 independent cohort studies with a total of 384 patients. The rate of technical success was 99.86 % (95 % CI: 99.2 %, 100 %; P = 0.00; I2  = 70.69 %) and the calculated pooled rate of clinical success was 84.99 % (95 % CI: 77.4 %, 91.41 %; P = 0.00; I2  = 68.02 %). The calculated pooled rate of adverse events was 7.6 % (95 % CI: 3.99 %, 12.21 %; P = 0.03; I2  = 42.5 %) with recurrent abscess formation and bleeding being the most common AEs. Moderate to substantial heterogeneity was noted in our meta-analysis.Conclusions Endoscopic vacuum therapy appears to be a minimally invasive, safe, and effective treatment modality for patients with a significant colorectal leak without any generalized peritonitis with high clinical and technical success rates and a low rate of adverse events. Further prospective or randomized controlled trials are needed to validate our findings.